2013
DOI: 10.3168/jds.2012-6417
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Rapid detection of milk fat adulteration with vegetable oil by fluorescence spectroscopy

Abstract: This study assessed the potential application of fluorescence spectroscopy in detecting adulteration of milk fat with vegetable oil and characterizing the samples according to the source of the fat. Pure butterfat was adulterated with different vegetable oils at various concentrations (0, 5, 10, 15, 20, 30, and 40%). Nonfat and reduced-fat milk were also adulterated with vegetable oils to simulate full-fat milk (3.2%). The 2- and 3-dimensional front-face fluorescence spectroscopy and gas chromatography were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 9 publications
2
49
0
Order By: Relevance
“…It has also been possible to detect multiple adulterants including ammonium sulfate, dicyandiamide, melamine and urea in milk powder using Raman chemical imaging (Qin et al 2013). Milk fat adulteration is also a very common concern, however, several techniques have been developed to detect the adulteration based on Butyro Refractometer (Arora et al 1996), fluorescence spectroscopy (Ntakatsane, Liu, & Zhou, 2013), derivative spectroscopy (Jirankalgikar & De, 2014) and Raman spectroscopy (Uysal, Boyaci, Genis, & Tamer, 2013).…”
Section: Milk Adulteration With Other Compoundsmentioning
confidence: 99%
“…It has also been possible to detect multiple adulterants including ammonium sulfate, dicyandiamide, melamine and urea in milk powder using Raman chemical imaging (Qin et al 2013). Milk fat adulteration is also a very common concern, however, several techniques have been developed to detect the adulteration based on Butyro Refractometer (Arora et al 1996), fluorescence spectroscopy (Ntakatsane, Liu, & Zhou, 2013), derivative spectroscopy (Jirankalgikar & De, 2014) and Raman spectroscopy (Uysal, Boyaci, Genis, & Tamer, 2013).…”
Section: Milk Adulteration With Other Compoundsmentioning
confidence: 99%
“…(110) Vegetable oil Due to higher price and increased demand, milk fat has been a target of the fraudulent practices, such as replacement with cheaper or more readily available non-milk fats of plant and animal origin. (111) Vegetable oils (VO) are commonly used for this purpose. Also, VO is used as a chief source of fat in synthetic milk.…”
Section: Downloaded By [Selcuk Universitesi] At 05:28 03 February 2015mentioning
confidence: 99%
“…Therefore, the adulteration of the VO can easily be detected by analyzing the fatty acid profile by gas chromatography. (111) Adulteration of milk with VO, also increases its Butyro Refracto meter reading, which is also a suitable measure for detection. (64) In India, Hydrogenated vegetable oil (HVO) is a common adulterant in milk fat.…”
Section: Downloaded By [Selcuk Universitesi] At 05:28 03 February 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…Direct analysis in real time (DART) ionisation coupled with high resolution mass spectrometry (DART-HRMS) was used by Hrbek et al (2014) to detect the presence of vegetable oils added to soft cheese which involves the use of costly DART-HRMS systems. The study conducted by Ntakatsane et al (2013) revealed that vegetable oils can be detected up to 5% level using fluorescence spectroscopy. There, thus, remains a need for a simple, quick, economic and reliable method for the detection of most of the vegetable oils even at lower levels in milk fat.…”
Section: Introductionmentioning
confidence: 99%